Reimagining Enterpreneurial Learning in the 21st century: A Conceptual Framework through STEAM Perspectives - Aryal , Rameshower (Journal of Kathmandu BernHardt College, 2025)
Traditional learning approaches to entrepreneurial education have no longer adequate to meet the energetic needs of learners and societies in the speedily evolving landscape of 21st century education. This conceptual paper try to enquiry the need to reimagine entrepreneurial learning by integrating interdisciplinary knowledge system in the different disciplines, creativity, innovation in learning and socio-cultural awareness. Drawing on existing theoretical model of transformative learning, constructivism, and entrepreneurial mindset of development, the study proposes a holistic framework that opinions entrepreneurial learning as a lifelong, learner-centered, and context-responsive learning process. The purposed framework in this article emphasizes experiential learning, critical thinking, innovation, and ethical engagement to equip learners with the capacities to navigate uncertainty, co-create value, and address complex global challenges. By shifting from a narrow focus on scheme creation to a broader paradigm of entrepreneurial thinking, this research aims to inform curriculum re-design, policy re-development, and pedagogical practice in higher University education and beyond. The study contributes to a future-oriented vision of entrepreneurial learning as a potency for inclusive and sustainable transformation for the learners of the 21st century.